Targeted plasma metabolome response to variations in dietary glycemic load in a randomized, controlled, crossover feeding trial in healthy adults1. Issue 9 (2nd September 2015) - Barton, Sally; Navarro, Sandi L.; Buas, Matthew F.; Schwarz, Yvonne; Gu, Haiwei; Djukovic, Danijel; Raftery, Daniel; Kratz, Mario; Neuhouser, Marian L.; Lampe, Johanna W.
<x xml:space="preserve">Abstract</x> Low versus high glycemic load (GL) diet patterns are inversely associated with obesity and chronic diseases such as cancer and cardiovascular disease.